Film As A Media For Propaganda That Can Damage Indonesia's National Order - Aisyah Izdihar Windani; Almuchalif Suryo; Totok Imam (Cita konsultindo, 2026)
This research article discusses how film as a medium for propaganda can damage the Indonesian national order. The purpose of this study is to analyze how film can be a tool to damage the Indonesian national order. This study uses a literature review study or literature review, researchers analyzed each data obtained from various sources such as journal articles, government documents, websites and interviews. The results, film can be a medium for propaganda that can divide the Indonesian national order if it contains fake news and the spread of hatred. In conclusion, film can be a strategic tool to introduce the richness of the nation's arts and culture if used appropriately. However, film can also be dangerous if it contains propaganda that can divide the Indonesian nation through the narrative conveyed so that it can indoctrinate its audience.